Current trends in the training of vocational education specialists in road transport - V. Pryimak (Mukachevo State University, 2023)
The research is devoted to the examination of the leading trends in the training of future specialists in the road transport sector. The relevance of the study is conditioned upon the need for a rapid response of modern educational institutions to the processes of globalisation and changes in global trends in the socio-economic, educational, scientific, information and other sectors. As one of the most influential sectors in the economy of each country, the road transport infrastructure requires high-quality training of competitive specialists and a constant search for ways to improve its efficiency. The purpose of the research is to explore, identify and substantiate several trends which affect the quality of specialist training or contribute to its improvement in line with the requirements of the times. The research analyses the relevant scientific literature and uses scientific methods of systematisation, comparative and structural analysis, generalisation, and specification. The research outlines the current trends in the professional training of road transport education specialists. The author summarises the main trends in the industry as an integral part of education in a multi-level system designed to provide the necessary theoretical and practical experience for future specialists with a focus on the most complete professional self-determination. The significance of the competence-based and practice-oriented approaches as the most important in the process of training a specialist is specified. The factors that influence the quality of training of competitive employees in the road transport sector, who will have the opportunity for decent employment and professional growth, are identified. It is concluded that the improvement of training of future specialists in the road transport industry in recent years is designed to integrate into the international educational space, to improve the quality of training in the production, economic, educational and scientific spheres. It is emphasised that high-quality training at all levels can be effective if all participants in the process are active. The practical significance of the research is the possibility of using the results obtained in planning new programmes for the training of future specialists in technical educational institutions, in organising the process of internships during training and advanced training of industry specialists.